Phytoclimatic versatility and potential diversity of natural arboreal forest cover in peninsular Spain (INVESTIGACION AGRARIA-SISTEMAS Y RECURSOS FORESTALES, 2008)
A multivariate methodology was assayed to evaluate the phytoclimatic versatility of peninsular Spain and how this relates to the potential diversity of natural tree covers. The instances of greatest phytoclimatic versatility occur in a range of altitude between 1000 and 1300 m; these are cool phytoclimates with only short, low-intensity periods of aridity. These factorial ambits of maximum versatility correspond chiefly to the substeppe nemoral subtype VI(VII), followed by genuine nemoral VI and humid nemoromediterranean VI(IV)(2) subtypes. The lowest values of versatility and potential diversity correspond to dry genuine Mediterranean (IV(1)) or transitional Mediterranean IV(VI)(1) subtypes and to alpine oroborealoid or oroarcticoid subtypes. In geographical terms, intermediate mountain areas in the north of the Peninsula and some massifs in the southern half score the highest in the Diversity Index used. The lowest scores are found in the southern half of the Peninsula, although in the northern half low scores are also found for littoral areas, interior areas of the Duero and Ebro basins and alpine areas. Autoecological phytoclimatic spectra headed by stands of Pinus nigra and Quercus petraea present the greatest phytoclimatic versatility, while those headed by Quercus ilex ballota and Pinus uncinata stands present the least versatility. This article offers new methodological horizons for the study of the effects of climate change on plant diversity.

Phytoclimatic characterization of holm-oak provenances (Quercus ilex L.) in the Central-Northern Iberian Peninsula (Forest Systems, 2002)
This paper presents some contributions to the phytoclimatic characterization of stands of holm-oak (Quercus ilex. L.) in the centre-north of the Iberian Peninsula and the testing of a method of phytoclimatic homologation applicable to the characterization of provenances of the species. For the phytoclimatic characterization, 432 sampling points in the Province of Burgos were considered, corresponding to the centres of cartographic tessellae of actual vegetation in which holm-oak was the principle species of the forest (18,965 ha). The phytoclimatic diagnosis followed the phytoclimatic models of Allué-Andrade. Phytoclimatic territorial models were constructed in digital format on the basis of preliminary territorial factorial estimations, which were used to determine phytoclimatic terns. Based on the establishment of phytoclimatic ambits for the existence of holm-oak stands in Burgos and stratification in accordance with the five phytoclimatic subtypes (VI(IV)1, VI(IV)2, VI(VII), VI(V) and VI), phytoclimatic homologation was performed in three phases of increasing strictness, all based on a comparison of phytoclimatic terns derived from the general and specific phytoclimatic systems. In the strictest homologation, an adequate and territorially compact degree of discrimination was achieved for 2.622.500 ha (Quercus ilex subsp. ballota) and 116.00 ha (Quercus ilex subsp. ilex) in the centre-north of the Iberian Peninsula. The marked edaphic azonality of the species was an important factor in the interpretation of the results.